Unloader brace or high tibial osteotomy in the treatment of the young patient with medial knee osteoarthritis: a randomized controlled trial. - STAM, Mark; VERSCHUEREN, Joost; VAN OUTEREN, Mark V.; BROUWER, Reinoud W.; GAASBEEK, Robert D. A.; BLENDEA, Sorin G.; VAN ES, Eline M.; REIJMAN, Max; BIERMA-ZEINSTRA, Sita M. A. (Acta Orthopaedica, 2025)
Background and purpose — For medial knee osteoarthritis (OA), operative and nonoperative treatment options are available. Two widely applied unloading therapies are a valgus unloader brace and a high tibial osteotomy (HTO). We aimed to compare the effects of a valgus unloader knee brace with an HTO on knee pain after 1 year in patients with symptomatic medial knee OA. Methods — We recruited patients from 9 Dutch hospitals between August 2014 and February 2019 for an open-labeled multi-center randomized controlled trial (Dutch Trial Register NL4200). Patients aged 18 to 65 years with symptomatic medial compartmental knee OA were randomized to either a valgus unloader brace or an HTO. The primary outcome was the pain subscale of the Knee injury and Osteoarthritis Outcome score (KOOS) after 1 year. Patients were evaluated at 3, 6, 9, 12, and 24 months. Results — 51 patients were included in the study, of whom 23 were randomized to the unloader brace and 28 to the HTO. The HTO, compared with the unloader brace, showed a significant and clinically relevant difference at 12 months of follow-up in KOOS pain of –28 (95% confidence interval –43 to –13). Conclusion — We found that, on group level, an HTO is more effective in reducing knee pain than an unloader brace after 12 months.